Ratcheting and fatigue-led wear in rail-wheel contact - FRANKLIN, F. J.; CHUNG, T.; KAPOOR, A. (Fatigue & fracture of engineering materials & structures, 2003)
ABSTRACT A computer model, which simulates the ratcheting wear of a ductile material subject to repeated loading, is presented and discussed in detail. Variation of material properties is a feature of the model, failure by ductility exhaustion occurring at isolated points or extending regions of failure. Such regions form crack‐like features. Mechanisms for removal of weakened material from the surface as wear debris are described. The wear process causes a degree of surface roughness. The simplicity of the model enables simulation of millions of load cycles in only a few hours' computer time. The computer model is used to study the effect of partial slip on wear rate. When creepage is relatively low, the wear rate increases sharply with creepage. When creepage is relatively high, the wear rate is largely insensitive to the creepage.